Elementary and simplified control of analog parallel buck converters - To, Mark Ryan S. (Animo Repository, 2010)
In this chapter, an elementary and simplified control of four analog parallel-connected buck converters was simulated in MATLAB/Simulink. These parallel converters, having the same values of inductances and capacitances but different parasitic resistances, were observed under various conditions of current sharing load and on the total number of active converters. The voltage and current errors of each converter were sampled and fed into a controller to regulate its output voltage. An elementary and simplified control was used to determine which converters will turn ON/OFF during a given current load. Between active converters sharing the load, the average current method was used. In this paper we conclude that an elementary and simplified control of parallel analog buck converters is feasible and achievable leading to a possibility of a much more enhanced and improved control of digital parallel converters. Simulation-demonstrated results are presented including the static and dynamic loading responses and current sharing error of the parallel system under different conditions.